2021
DOI: 10.3233/jifs-189196
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus Islamic bank efficiency: A dynamic network data-envelopment-analysis approach

Abstract: This study compares the efficiency of conventional and Islamic banks in Malaysia by engaging in a dynamic three-step (production, intermediation, and profitability) network data envelopment analysis (DEA). The inputs and outputs for the DEA model are selected based on the CAMELS rating. The major contributions of this study are threefold. First, this study investigates the efficiency of Malaysian banks using a novel dynamic network DEA model. Second, the Malaysian banking industry is found to be efficient in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The mixed efficiency findings with respect to different types of efficiencies (i.e., OTE, PTE, SE, CE, PE, RE and AE) fall into several categories depending on the feature or characteristic under consideration (i.e., bank type: Islamic vs Conventional; and ownership type: foreign vs domestic) and could be summarised as follows: (a) Islamic banks are more efficient than Conventional banks; (b) Islamic banks are less efficient than Conventional banks; (c) there is no significant difference in efficiency between Islamic banks and their Conventional counterparts; (d) domestic Islamic banks are more efficient than foreign Islamic banks; and (e) domestic Islamic banks are less efficient than foreign Islamic banks. As an illustration of these conflicting results, Ahmad and Luo (2010), Shawtari et al (2015), Yilmaz and Güneş (2015), Batir et al (2017), Erfani and Vasigh (2018), Prima Sakti and Mohamad (2018), Musa et al (2020) and Azad et al (2021) revealed that Islamic banks are more overall technically efficient than Conventional banks, whilst Mokhtar et al (2007Mokhtar et al ( , 2008, Ahmad and Abdul Rahman (2012), Mobarek and Kalonov (2014), Abbas et al (2016), Majeed and Zanib (2016), Abdul-Wahab and Haron (2017), Doumpos et al (2017), Shah and Masood (2017), Kaffash et al (2018), Khan et al (2018), Haque et al (2020), Alsharif (2021) and Azad et al (2021) came to the opposite conclusion. Other studies found a non-significant association (Grigorian andManole, 2005, Shahid et al, 2010;Yahya et al, 2012;Asmild et al, 2019;Shahwan and Habib, 2021).…”
Section: Critical Analysis Of the Islamic Banking Efficiency Literatu...mentioning
confidence: 99%
See 3 more Smart Citations
“…The mixed efficiency findings with respect to different types of efficiencies (i.e., OTE, PTE, SE, CE, PE, RE and AE) fall into several categories depending on the feature or characteristic under consideration (i.e., bank type: Islamic vs Conventional; and ownership type: foreign vs domestic) and could be summarised as follows: (a) Islamic banks are more efficient than Conventional banks; (b) Islamic banks are less efficient than Conventional banks; (c) there is no significant difference in efficiency between Islamic banks and their Conventional counterparts; (d) domestic Islamic banks are more efficient than foreign Islamic banks; and (e) domestic Islamic banks are less efficient than foreign Islamic banks. As an illustration of these conflicting results, Ahmad and Luo (2010), Shawtari et al (2015), Yilmaz and Güneş (2015), Batir et al (2017), Erfani and Vasigh (2018), Prima Sakti and Mohamad (2018), Musa et al (2020) and Azad et al (2021) revealed that Islamic banks are more overall technically efficient than Conventional banks, whilst Mokhtar et al (2007Mokhtar et al ( , 2008, Ahmad and Abdul Rahman (2012), Mobarek and Kalonov (2014), Abbas et al (2016), Majeed and Zanib (2016), Abdul-Wahab and Haron (2017), Doumpos et al (2017), Shah and Masood (2017), Kaffash et al (2018), Khan et al (2018), Haque et al (2020), Alsharif (2021) and Azad et al (2021) came to the opposite conclusion. Other studies found a non-significant association (Grigorian andManole, 2005, Shahid et al, 2010;Yahya et al, 2012;Asmild et al, 2019;Shahwan and Habib, 2021).…”
Section: Critical Analysis Of the Islamic Banking Efficiency Literatu...mentioning
confidence: 99%
“…The different groups of banks that have been compared were chosen based on (1) the type of bank; i.e., Islamic vs. Conventional banks (e.g., Grigorian and Manole, 2005;Kaffash et al, 2018;Wanke et al, 2019;Azad et al, 2021), (2) the type of operating structure (modus operandi) of the bank; i.e., fully-fledged Islamic banks vs. Islamic windows (e.g., Mokhtar et al, 2007;Salami and Adeyemi, 2015), where Islamic windows refer to Conventional banks offering Islamic banking products and services, and (3) the geographic location or countries they operate in, which could be divided into four main categories: (a) the first category consists of single country-focused studies (e.g., Mokhtar et al, 2007;Yilmaz and Güneş, 2015;Abdul-Wahab and Haron, 2017), (b) the second category consists of multi-country focused studies (e.g., Grigorian and Manole, 2005;Noor and Ahmad, 2012a;Wanke et al, 2019), (c) the third category consists of regional focused studies (e.g., Al-Muharrami, 2008;Alqahtani et al, 2017;Zeineb and Mensi, 2018), and (d) the fourth and last category consists of multi-region focused studies comparing the efficiency scores of Islamic banks in different regions (e.g., Yudistira, 2004;.…”
Section: A Types Of Efficiencies Their Analyses and Their Driversmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of the research has the following limitations: First, the internal structure of decision-making units (DMUs) is often overlooked; second, undesirable outputs often cannot be considered. Wang et al (2014) claimed that the Chinese commercial banking system has a two-stage internal structure [21]; Azad et al (2021) [22], Tan et al (2021) [23], and Yang et al (2023) [24] all emphasized that it is necessary to consider the internal system structure of banks when evaluating their efficiency; otherwise, the accuracy of commercial bank efficiency evaluation would be affected. Safiullah and Shamsuddin (2022) [25], Shah et al (2022) [26], and Wanke et al (2023) [27] all claimed that nonperforming loans should be considered undesirable outputs in the efficiency evaluation of commercial banking because they represent the risks of commercial banking and hinder its sustainable development.…”
Section: Introductionmentioning
confidence: 99%